Materializing Democracy : Toward a Revitalized Cultural Politics - Nelson, Dana D.; Castronovo, Russ, 1965- (Book collections on Project MUSE., 2002)
Investigates the complex histories and conflicting desires that are generally concealed behind the term "democracy."